PENGARUH PENGGUNAAN FITUR PELATIHAN MANDIRI PADA PLATFORM RUANG GTK TERHADAP KOMPETENSI PEDAGOGIK GURU KELAS SEKOLAH DASAR DI KECAMATAN MANGGALA KOTA MAKASSAR - Djabir, Rosani; Pada, Amir; Muhammad Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the use of the Self-Training feature on the Ruang GTK Platform on the pedagogical competence of elementary school teachers in Manggala District, Makassar City. The research method used is descriptive quantitative with a correlational approach. Data were collected through questionnaires and interviews with 75 teachers. The results showed that both the use of the Self-Training feature and teachers’ pedagogical competence were in the high category. Regression analysis revealed a positive and significant influence between the two variables, with a contribution of 46%. These findings support digital platforms as effective tools for teacher professional development.